Improving case study research in medical education: a systematised review. Issue 5 (27th November 2017) - Cheek, Colleen; Hays, Richard; Smith, Janie; Allen, Penny
Abstract : Context: Case study research (CSR) is a research approach that guides holistic investigation of a real phenomenon. This approach may be useful in medical education to provide critical analyses of teaching and learning, and to reveal the underlying elements of leadership and innovation. There are variations in the definition, design and choice of methods, which may diminish the value of CSR as a form of inquiry. Objectives: This paper reports an analysis of CSR papers in the medical education literature. The review aims to describe how CSR has been used and how more consistency might be achieved to promote understanding and value. Methods: A systematised review was undertaken to quantify the number of CSR articles published in scholarly medical education journals over the last 10 years. A typology of CSR proposed by Thomas and Myers to integrate the various ways in which CSR is constructed was applied. Results: Of the 362 full‐text articles assessed, 290 were excluded as they did not meet the eligibility criteria; 76 of these were titled 'case study'. Of the 72 included articles, 50 used single‐case and 22 multi‐case design; 46 connected with theory and 26 were atheoretical. In some articles it was unclear what the subject was or how the subject was being analysed. Conclusions: In this study, more articles titled 'case study' failed than succeeded in meeting the eligibility criteria. Well‐structured, clearly written CSR in medical education has the potential to increase understanding of more complex situations, but this review shows there is considerable variation in how it is conducted, which potentially limits its utility and translation into education practice. Case study research might be of more value in medical education if researchers were to follow more consistently principles of design, and harness rich observation with connection of ideas and knowledge to engage the reader in what is most interesting. Abstract : Case study research (CSR) is suggested as capable of providing more value in medical education if researchers more consistently followed principles of design and reporting.